Study on low rate of change characteristics of saturation output current of 28 nm UTBB FDSOI at 300 °C high-temperature. (16th February 2023) - Xu, L D; Gao, L C; Ni, T; Wang, J J; Zhao, S S; Zhang, H Y; Li, Y F; Wang, R J; Li, X J; Yan, W W; Li, D L; Bu, J H; et al.
Abstract: Partially-depleted silicon-on-insulator (PDSOI) MOSFETs with full dielectric isolation structure are widely used in the high temperature field of 225 °C, but affected by the threshold voltage and carrier mobility, the saturated output current has a rate of change as high as 24.9% at 25 °C–300 °C, which will reduce the working speed and accuracy of the analog circuit. This paper studies the high temperature output current characteristics of ultra-thin body and buried oxide (UTBB) fully-depleted silicon-on-insulator (FDSOI) MOSFETs with the 28 nm low voltage threshold structure. The experimental results show that when the gate voltage of the device is constant, the saturation current change of 28 nm short-channel FDSOI device is 1.93% in the temperature range from 25 °C to 300 °C, which is 12.9 times more stable than that of 0.13 μ m PDSOI device, 4.5 times and 8.4 times higher than that of 0.3 μ m and 2 μ m long-channel FDSOI device. When the gate voltage of the device drifts from the zero-temperature coefficient (ZTC) point by ±10%–±20%, the output current change of the short-channel FDSOI device is still the lowest. It is proved by theory and simulation that the low temperature change rate of the carrier velocity of the short-channel FDSOI device is the main factor affecting the stability of the output current. From the analysis of the saturation current model and the ZTC operating point, reducing the gate operating voltage of the device or increasing the threshold voltage of the device can further improve the stability of the output current at high temperatures. The research in this paper proves that the 28 nm UTBB FDSOI device has good high temperature saturation current stability, which can well meet the output current stability requirements of high temperature analog circuits.